The Analysis of The Pacing Profiles Based on The Performance Level of The Finishers in The Istanbul Marathon - Celil Kaçoğlu (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to determine, on the basis of performance levels, running pace profiles of the male runners (n=2095) who completed the 40th International Istanbul Marathon in less than 6 hours. While 0-35 km of the marathon was divided into 5 km long sections, 35-42.2 km of it was determined as the last segment which was 7.2 km. The average speeds of the running pace of the athletes in the determined segments were calculated. Performance groups were evaluated in 8 different groups with the athletes completing the race in the finishing time slower than the winner’s race time. The difference between performance groups and successive segments was evaluated with Mixed Anova. The results of the Mixed Anova analysis showed that there were statistically significant differences between inter-segments race profiles depending on the performance level (p lt;0.000). Overall, the athletes showed an increasing pace in all the performance groups in the first ten kilometers of the race (p lt;0.001). The highest level of the performance group showed an even pace in the segments between 10 and 25 km, while it fell between 25 and 30 km and continue at this level between 30 and 35 km. In other groups, it was observed that the speeds fell inversely proportional to the performance in the segments between 10 and 35 km (p lt;0.05). In the last 7.2 km segment, it was observed that the athletes with the highest level of performance had a decrease in pace and the rate of decrease in the pace was lower in the groups with lower performance level. Only in the slowest group of athletes, the pace was observed to increase in the last segment. Considering the whole race, it was seen that the athletes showed a pace profile close to the positive pace profile in general.